The high-temperature degradation mechanism of W-core SiC fibers. Issue 2 (February 2023) - Wu, L.J.; Zhang, Y.; Zhang, K.; Huang, H.; Wang, M.J.; Wang, L.P.; Qi, J.L.; Lin, J.Y.; Wen, M.
Abstract: Continuous W-core SiC fiber has been regarded as a promising reinforcement, exhibiting huge potential for applying to hypersonic aircraft commonly suffering from harsh environment with high-temperature short-term characteristic. In this work, the micro/nano-scale investigation on heat treatment (HT) induced dynamic evolution of microstructure in W-core SiC fiber was performed to reveal strength degradation mechanism. It is revealed that the integrity of surface C coating can be well retained even after 1400 ℃/2 h HT avoiding the appearance of surface-dominated fracture mode. In the SiC sheath, only defects annihilation and crystallization transiting the disorder structure into well-crystallized β-SiC columnar grains instead of excessive growth happens, and thus HT induced sharp strength degradation cannot be governed by the microstructural variation of SiC sheath. After high-temperature HT, the interfacial reaction layer continuously thickens with increasing HT temperature that is proportional to fracture mirror zone radius, responsible for strength degradation induced by high-temperature short-term HT.